Accuracy of patient-specific instrumentation in total ankle arthroplasty: A comparative study. Issue 3 (June 2019) - Saito, Guilherme H.; Sanders, Austin E.; O'Malley, Martin J.; Deland, Jonathan T.; Ellis, Scott J.; Demetracopoulos, Constantine A.
Highlights: Patient-specific instrumentation in TAA provides similar accuracy as standard instrumentation in terms of tibial component alignment. Patient-specific instrumentation preoperative reports are poor predictors of implant sizing. Surgeon's experience should always guide the final decision to avoid errors in sizing and positioning of the implant. Abstract: Background: Patient-specific instrumentation (PSI) for TAA is a novel technology with several potential benefits. The primary goal of this study was to compare the use of PSI with the standard referencing guide (SRG) in regards to accuracy of tibial implant positioning. Operative time, fluoroscopy time and accuracy of PSI preoperative reports were also evaluated. Methods: A retrospective analysis of 99 patients who underwent a primary TAA with the INFINITY prosthesis (Wright Medical, Memphis, TN) was performed. Patients were divided in two groups based on the type of instrumentation used during the TAA (75 in the PSI group vs 24 in the SRG group). There was no significant difference between groups in regards to age at the time of surgery ( P  = 0.122), sex ( P  = 0.138), number of concomitant procedures performed during surgery ( P  = 0.567) and etiology ( P  = 0.841). However, preoperative deformity was significantly smaller in the PSI group ( P  = 0.002). Results: Tibial implant positioning was similar between groups. In the coronal plane, the absolute deviation of the tibial implant from the intended alignment was 1.7 ± 1.4° for the SRG and 1.6 ± 1.2° for PSI ( P  = 0.710). In the sagittal plane, the absolute alignment deviation of the tibial implant was 1.8 ± 1.4° for the SRG and 1.9 ± 1.5° for PSI ( P  = 0.675). Operative time (167 vs 190 min, P  = 0.040) and fluoroscopy time (85 vs 158 s, P <  0.001) were significantly decreased in the PSI group. The PSI preoperative plan report correctly predicted the implant size in 73% of cases for the tibial component and in 51% of cases for the talar component. Conclusions: PSI provided similar tibial component alignment as standard instrumentation. Additionally, PSI preoperative plan reports were poor predictors of implant sizing. Therefore, the final decision should always be based on surgeon's experience in order to prevent errors in implant sizing and positioning. Level of evidence: Level III, retrospective comparative study.